ANALISIS STATUS KEBERLANJUTAN EKOWISATA MANGROVE MUNDU, DESA MUNDU PESISIR, KECAMATAN MUNDU, KABUPATEN CIREBON - Ardhiansyah, Rasendriya Naufal; Prihadi, Donny Juliandri; Mulyani, Yeni; Pamungkas, Wahyuniar; Saptari, Muhammad Khairan; Zendina, Luthfia (Jurnal Perikanan Unram, 2025)
Mundu Mangrove Ecotourism is located in Mundu Pesisir Village, Mundu District, Cirebon Regency. Ecotourism is a form of tourism that is managed through a conservation approach. This study aims to analyze the sustainability status of mangrove ecotourism based on five dimensions of ecology, economy, socio-culture, infrastructure, and institutional law using the RAPFISH approach, identify critical attributes that affect sustainability, and formulate mangrove ecotourism development strategies in Mundu Pesisir Village. Data were collected through field surveys, interviews, and questionnaires to various stakeholders, then analyzed using the Multidimensional Scaling (MDS) method through RAPFISH (Rapid Appraisal Technique for Evaluating Fisheries Sustainability). The results of the sustainability analysis based on 5 dimensions, namely the ecological dimension of 48.33 (less sustainable), the economic dimension of 22.05 (unsustainable), the socio-cultural dimension of 53.13 (moderately sustainable), the infrastructure dimension of 32.14 (less sustainable), and the institutional legal dimension of 76.03 (sustainable). The results of the analysis show that there are still many things that need attention to improve the sustainability score, especially in dimensions that still get a small score.